The correlation between children’s own health control and their health perceptions and behaviours, and the associated factors (Acta Scientiarum. Health Sciences, 2021)
The study was conducted as a correlational descriptive study to determine the correlation between children’s own health control and their health perceptions and behaviours, as well as the associated factors. The sample of the study consisted of 963 children in the age group of 7-12 years studying at one primary schools affiliated with the Ministry of National Education. It was determined that age affected health control and health perception and behaviours in children. A positive significant correlation was found between the health locus of control and health perceptions and behaviours of the children. The children had positive health behaviours, and they had high internal control in their own health management. In accordance with these results, children’s own health management should be increased to increase their positive perceptions and behaviours.